If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3(8x + 1y) = 24 6x + (8x * 3 + 1y * 3) = 24 6x + (24x + 3y) = 24 Combine like terms: 6x + 24x = 30x 30x + 3y = 24 Solving 30x + 3y = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 30x + 3y + -3y = 24 + -3y Combine like terms: 3y + -3y = 0 30x + 0 = 24 + -3y 30x = 24 + -3y Divide each side by '30'. x = 0.8 + -0.1y Simplifying x = 0.8 + -0.1y
| 5x+20y=-400 | | 0=-2/3x-4 | | 10(s-6)=-109 | | 21+3x=-4 | | X^2+4x+4(10)=40(2+x) | | 13/2x3/1 | | 8/9-4/5(1/3)^2 | | 5x-3x+2=x+15 | | x^4+3x^3-2x-3=3 | | 35.94+73.06-x-57=37 | | 70x=488 | | 35+3x-11=32 | | 1260/900 | | 6(2070+w)=12810 | | 5(f-7)=-7 | | 0-0=1 | | 3(2x+1)=4x-8 | | 8-4w/3= | | 12/1x1/2 | | 53.3(.5-x)(.5-x)=(2x)(2x) | | 0.33333333333333x-11=2 | | T-3a=9 | | 13e-6-10e+4= | | 4x+24=3x+12 | | m/7=7/4 | | 73+(x-11)+x=180 | | n÷3/4=12 | | 60/1x1/5 | | 6x+-6=15x+15 | | 4/3•3.14•6•6•6 | | 5=x-6x | | 15/[9^2/(8-5)-(-7)] |